2019
DOI: 10.1111/papr.12847
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Fibromyalgia Reporting Severe Pain but Low Impact of the Syndrome: Clinical and Pain‐Related Cognitive Features

Abstract: Background Fibromyalgia (FM) is a prevalent and highly disabling chronic pain syndrome. However, differences among patients regarding how pain impacts on daily life are remarkable. The main aim of this study was to identify clinical and pain‐related cognitive variables characterizing patients reporting high adaptability despite experiencing severe chronic pain. Methods Two hundred and eighty‐three Spanish patients with FM with high levels of pain were classified into 2 groups: (1) those reporting low impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 26 publications
5
31
0
Order By: Relevance
“…In the cross-sectional study, higher age, high educational level, work, no depression and lower degree of illness (Fibromyalgianess Score) were found associated with the outcome, lower FIQ score, i.e., better daily functional level and lower symptoms in patients with fibromyalgia. Previous studies have identified high age, low educational level and low socioeconomic status as associative factors for fibromyalgia [39,41], and depression has been found to bea common comorbidity as well as associated with a higher impact of the illness [42]. The mean values of FIQ total do not change substantially from T1 to T2.…”
Section: Discussionmentioning
confidence: 84%
“…In the cross-sectional study, higher age, high educational level, work, no depression and lower degree of illness (Fibromyalgianess Score) were found associated with the outcome, lower FIQ score, i.e., better daily functional level and lower symptoms in patients with fibromyalgia. Previous studies have identified high age, low educational level and low socioeconomic status as associative factors for fibromyalgia [39,41], and depression has been found to bea common comorbidity as well as associated with a higher impact of the illness [42]. The mean values of FIQ total do not change substantially from T1 to T2.…”
Section: Discussionmentioning
confidence: 84%
“…In this sense, the psychological flexibility model suggests that cognitive fusion would explain the inability of some individuals to implement adaptive coping methods in the presence of pain or related symptomatology [15]. Indeed, there is evidence to support the influence of cognitive fusion on outcomes in patients with FM [16,17]. Research supports the idea that both processes are distinct and that they could potentially interact and influence each other [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the light of the previous literature [1,7,8,13,17], our goals is to test the hypothesized associations of pain catastrophizing, cognitive fusion, and FM symptom severity (pain, fatigue, and depression) in a theoretically-sound model that accounts for the contribution of these elements altogether in relation to functional limitation. We hypothesize that catastrophizing components and cognitive fusion will be associated with greater disability (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgia (FM) is a rheumatic disease characterized by a history of widespread musculoskeletal chronic pain, sleep disturbance, debilitating fatigue, joint stiffness, and cognitive (memory, attention, perception, coordination) dysfunction and is frequently associated with depression and anxiety-related disorders [ 1 3 ]. FM is a very prevalent disease worldwide, with estimates suggesting that between 2% and 5% of individuals, mostly females, experience this syndrome globally [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%